Translation strategies of cultural words in Tarian Bumi novel and its translation - Robingah; Ahmad Jum'a Khatib Nur Ali (LADU: Journal of Languages and Education, 2021)
Background: Translation is an activity of changing meaning from source language into target language. There are a lot of problems encounter by the translator in translating text such as problem in translating literature text, cultural items, idiomatic expression, and many others. Tarian Bumi is an Indonesian novel written by Oke Rusmini where in the novel there are a lot of cultural words, cultural items, especially Balinese culture. Purpose: The purposes of this research article are to categorize the cultural words using Newmark’s theory and to analyze the translation strategies of those cultural words in Tarian Bumi novel and its translation. Design and methods: This research article applied qualitative methods and using documentation technique in collecting the data. In categorizing the cultural words, Newmark’s theory is applied. To find out the translation strategies used by the translator, the theory of Baker of Translation strategy is used. Results: The cultural words found in Tarian Bumi novel and its translation are 58 data. From Newmark’s theory of cultural words category, there are 4 categories found, they are: ecology with 1 data, material culture with 14 data, social culture with 6 data, and organization, concept, ideas with 35 data. After the data are categorized based on the cultural category, then writer analyzed the translation strategies. The result is there are only 5 translation strategies found. The strategies found are: 1) translation by more general word 9 data, 2) translation by using cultural substitution 12 data, 3) translation by using loan word or loan word plus explanation 25 data, 4) descriptive equivalent 11 data, 5) translation by omission with only 1 data.